Coastal proximity and individual living standards: Econometric evidence from georeferenced household surveys in sub-Saharan Africa - Frederik Wild; David Stadelmann (Review of Development Economics, 2022)
We investigate georeferenced household-level data consisting of up to 128,609 individuals living in 11,261 localities across 17 coastal sub-Saharan African countries over 200.167emyears. We analyze the relevance of coastal proximity, measured by the geographic distance to harbors, as a predictor of individual economic living standards. Our setting allows us to account for country-time fixed effects as well as individual-specific controls. Results reveal that individuals living further away from the coast are significantly poorer, measured along an array of welfare indicators. Our findings are robust to the inclusion of other geographic covariates of development such as climate (e.g., temperature, precipitation) or terrain conditions (e.g., ruggedness, land suitability). We also explore mechanisms through which coastal proximity may matter for individual welfare and decompose the estimated effect of coastal proximity via formal mediation analysis. Our results highlight the role of human capital, urbanization, and infrastructural endowments in explaining within-country differences in individual economic welfare.
Keywords: 330; coastal proximity; geography; mediation analysis; sub-Saharan Africa